The Use of Learning Logs Strategy in Improving Students’ Ability in Writing Expository Paragraph - Agung Prasetyo Wibowo; Vonnysa Febrinda (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2019)
To see the difference in students' ability in writing expository paragraphs, this research uses a comparison between log learning and conventional learning strategies. Using true-experimental research, there were pre-test, treatment, and post-test. The subject of this research was the first-year students of State Senior High School 1 Selatpanjang, Meranti Island Regency. Two classes were deployed; an experimental and a control class with total of 47 students. The researchers used cluster random sampling, based on the group. In collecting data, the researchers used a test and an observation list. In assessing students’ writing, the researchers invited two raters, those who are qualified and considered as experts in teaching writing. The researchers analyzed the data by using t-test formula. The result shows that the mean score of students’ post-test in the control class was 65,5. Meanwhile, the mean score of students’ post-test in experimental class was 73,4. The result of t test sees a significant difference between students’ ability in writing expository paragraphs by using Learning Logs Strategy and those using Conventional Strategy (5.26). This result was higher than t table significant 5% (2,02) and 1% (2,69). H0 was rejected and Ha was accepted. It means that there was a significant difference in students’ ability in writing an expository paragraph using Conventional Strategy and using Learning Logs Strategy.